Processing/microstructure relationships in melt compounded polyamide 6 with different molecular weights: Effect of screw speed and viscosity ratio - Cravero, Fulvia; Arrigo, Rossella; Frache, Alberto (Polymer engineering and science, 2025)
In this work, the relationships between the processing parameters and the microstructure in melt‐compounded polyamide 6 (PA6) are investigated. To this aim, two PA6 having different viscosities are processed in a twin‐screw extruder at two different screw speeds (150 or 300 rpm) and characterized through rheological and thermal analyses. Furthermore, the thermo‐mechanical field along the screw is simulated using Ludovic® software, and the obtained results in terms of shear rate, residence time, and actual temperature are exploited to disclose interesting processing/microstructure relationships. In particular, the antagonistic role of the flow‐induced crystallization (FIC) and memory effect in governing the final microstructure is assessed. Specifically, for high screw speed and viscosity, FIC outweighs the memory effect due to the higher shear rate and temperature experienced by the material during processing. Besides, the dominant influence of FIC over the memory effect is found to be responsible for the higher overall crystallinity and α/γ content observed for the materials processed at 300 rpm. Finally, the same analyses are performed on blends containing different relative contents of the two PA6, demonstrating the interdependency of the screw speed and viscosity effects on the resulting microstructure. Highlights Processing parameters/microstructurerelationships for PA6 are investigated. PA6 with different viscosities wasmelt compounded using two screw speeds. Shear rate, temperature and residencetime during the processing were simulated. Screw speed and viscosity affectflow‐induced crystallization and memory effect. High screw speed and viscositypromoted FIC over the memory effect. Effect of melt viscosity and processing parameters on microstructure of polyamide 6.